The gendered production of food-related identities as interactional phenomena: an investigation of talk-in-interaction at the South African braai - Lewis, Ilse (My University, 2018)
This study explores the intersectional production of the social categories of gender and foodrelated identities, as they emerge as interactional phenomena. The dataset consists of approximately five hours of recorded participant interactions at a residential braai – a common social event in the lives of everyday South Africans. My analysis follows feminist conversation analytic principles, and demonstrates how participants establish and manage their food-related identities, as intersecting with gender, in interaction. It illustrates how various interactional strategies are employed toward managing potential incipient identity-related interactional conflict. This systematically results in the achievement of group solidarity, whilst steering the interaction away from confronting the wider-ranging ideological concerns that underpin this potential conflict in the first place. Thus, the wider political; environmental; and socioeconomic matters related to individual choices regarding food consumption, are effectively abandoned in interaction, and thus left uncontested. I conclude with a discussion regarding the implications of these findings for the everyday resistance of dominant cultural discourse, related to the gendered politics of food consumption
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Arts in Social and Psychological Research March 2018
Keywords: Conversation analysis; Oral communication; Free indirect speech